SIMKIM VERSION 2.0 PERFORMANCE REVIEW ON IMMIGRATION SUPERVISION IN THE NON TPI AGAM CLASS 2 IMMIGRATION OFFICE - Naufal Fauzi Rahman (Polteknik Imigrasi, 2020)
The development of information technology that is very fast and unpredictable is an important thing to pay attention to and also to be generally used and better in daily use. The immigration information technology in its implementation which uses an application called SIMKIM or the Immigration Management Information System. Immigration monitoring activities require the assistance of the SIMKIM application which is the main topic of this qualitative research which results in several conclusions including that the SIMKIM application has an important role in the implementation of immigration supervision, but the SIMKIM application can still be developed better in order to advance the Immigration agency even better.